Which Aspects of Postural Control Differentiate between Patients with Parkinson’s Disease with and without Freezing of Gait? - Griet Vervoort; Evelien Nackaerts; Farshid Mohammadi; Elke Heremans; Sabine Verschueren; Alice Nieuwboer; Sarah Vercruysse (Parkinson's Disease)
This exploratory study aimed to identify which aspects of postural control are able to distinguish between subgroups of patients with Parkinson’s disease (PD) and controls. Balance was tested using static and dynamic posturography. Freezers (n=9), nonfreezers (n=10), and controls (n=10) stood on a movable force platform and performed 3 randomly assigned tests: (1) sensory organization test (SOT) to evaluate the effective use of sensory information, (2) motor control test (MCT) to assess automatic postural reactions in response to platform perturbations, and (3) rhythmic weight shift test (RWS) to evaluate the ability to voluntarily move the center of gravity (COG) mediolaterally and anterior-posteriorly (AP). The respective outcome measures were equilibrium and postural strategy scores, response strength and amplitude of weight shift. Patients were in the “on” phase of the medication cycle. In general, freezers performed similarly on SOT and MCT compared to nonfreezers. Freezers showed an intact postural strategy during sensory manipulations and an appropriate response to external perturbations. However, during voluntary weight shifting, freezers showed poorer directional control compared to nonfreezers and controls. This suggests that freezers have adequate automatic postural control and sensory integration abilities in quiet stance, but show specific directional control deficits when weight shifting is voluntary.